Socialization of the Use of Larvicides as a Strategy to Overcome the Increase in Dengue Fever Cases in Darmasaba Village, Abiansemal District, Badung Regency, Bali Province - Sugiantiningsih, Anak Agung Putu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the effectiveness of a larvicide socialization program as a strategy to address the increasing number of Dengue Hemorrhagic Fever (DHF) cases in Darmasaba Village, Abiansemal District, Badung Regency. This qualitative study, using a case study design, employed data collection methods through in-depth interviews, observation, and document analysis. Respondents were selected using purposive sampling, including health officials, village officials, and community members. The results show that the socialization, including the direct distribution of larvicides to residents' homes, was effective in increasing community understanding and active participation. A positive change in behavior was observed, with residents routinely cleaning water containers and using larvicides, which contributed to a decrease in DHF cases. Nevertheless, challenges such as misconceptions about fogging being the only solution and resource limitations were still found. This study recommends stronger collaboration between the government, health workers, and the community, as well as the use of digital media to ensure the sustainability of the program